Socioeconomic inequities in specialized health services use following COVID-19 in individuals from Southern Brazil - Yohana Pereira Vieira; Juliana Quadros Santos Rocha; Rinelly Pazinato Dutra; Lorrany da Silva Nunes; Suele Manjourany Silva Duro; Mirelle de Oliveira Saes (BMC, 2023)
Abstract Background Evidence on inequalities in the health services use is important for public policy formulation, even more so in a pandemic context. The aim of this study was to evaluate socioeconomic inequities in the specialized health use services according to health insurance and income, following COVID-19 in individuals residing in Southern Brazil. Methods This was a cross-sectional telephone survey with individuals aged 18 years or older diagnosed with symptomatic COVID-19 using the RT-PCR test between December 2020 and March 2021. Questions were asked about attendance at a health care facility following COVID-19, the facilities used, health insurance and income. Inequalities were assessed by the following measures: Slope Index of Inequality (SII) and Concentration Index (CIX). Adjusted analyses were performed using Poisson regression with robust variance adjustment using the Stata 16.1 statistical package. Results 2,919 people (76.4% of those eligible) were interviewed. Of these, 24.7% (95%CI 23.2; 36.3) used at least one specialized health service and 20.3% (95%CI 18.9; 21.8) had at least one consultation with specialist doctors after diagnosis of COVID-19. Individuals with health insurance were more likely to use specialized services. The probability of using specialized services was up to three times higher among the richest compared to the poorest. Conclusions There are socioeconomic inequalities in the specialized services use by individuals following COVID-19 in the far south of Brazil. It is necessary to reduce the difficulty in accessing and using specialized services and to extrapolate the logic that purchasing power transposes health needs. The strengthening of the public health system is essential to guarantee the population's right to health.